Anmeldelser - Everett, Paul J. (Danish Yearbook of Musicology, 1991)
Review of: Peter Ryom: Repertoire des Œuvres d’Antonio Vivaldi. Les compositions instrumentales. Engstrøm & Sødring. Copenhagen 1986.